Development of Fine Motor Skills in Early Childhood Through Beading Activities at Imanuel Christian Preschool Palangka Raya - Resa Agustina; Wirastiani Binti Yusuf; Agus Sutrisno Muljono (Jurnal Indonesia Sosial Sains, 2026)
Fine motor development is an essential aspect of early childhood growth because it supports children's ability to control hand and finger movements, coordinate eye and hand movements, and perform daily activities independently. However, learning practices at Imanuel Christian Kindergarten Palangka Raya still show limitations in providing varied and stimulating activities, causing some children to experience difficulties in precision, coordination, and concentration. This study aims to describe the development of fine motor skills in early childhood and analyze the implementation of beading activities (meronce) as a learning strategy to stimulate fine motor development at Imanuel Christian Kindergarten Palangka Raya. This study employed a qualitative descriptive approach. Data were collected through non-participant observation, semi-structured interviews, and documentation involving one classroom teacher and children aged 5–6 years. Data analysis was conducted using the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion verification. The results showed that beading activities contributed positively to children's fine motor development. Through five learning meetings with different themes, children demonstrated gradual improvements in eye-hand coordination, finger flexibility, accuracy, concentration, creativity, and independence. The implementation of beading activities was carried out systematically through preparation, teacher demonstration, children’s practice, and evaluation. Supporting factors included teacher guidance, attractive learning materials, and children's motivation, while inhibiting factors involved differences in children's initial abilities and concentration levels. In conclusion, beading activities are effective as a meaningful and enjoyable learning medium for stimulating fine motor development in early childhood. This activity is recommended as an alternative learning strategy to support children's developmental needs.